052 How much weight loss is required to reduce intracranial pressure in idiopathic intracranial hypertension?. Issue 6 (27th May 2022) - Mollan, Susan; Mitchell, James; Ottridge, Ryan; Yiangou, Andreas; Cartwright, David; Grech, Olivia; ,; Tahrani, Abd; Brock, Kristian; Sinclair, Alex
Abstract : Background: The amount of weight loss required in idiopathic intracranial hypertension to reduce intrac- ranial pressure (ICP) has not been established. Methods: Using the IIH:weight trial data from 66 active patients randomised to bariatric surgery or community weight management intervention (CWI) (1:1) a linear hierarchical regression model was used to fit to the trial outcomes, adjusted for time, treatment arm, and body weight. This enabled prediction of ICP. Results: The greater the reduction in ICP was predicted with greater weight loss, with 24% weight loss resulting in normalisation of ICP in this population. The effect on ICP further improves between 12 to 24 months as the participants continue to lose weight. For expected ICP values to cross the threshold for normal, at 25cmCSF within 2 years, it is generally required that the patient would be allocated to the bariatric surgery arm and achieve a weight of 110kg. Those with a higher starting weight needed to lose more weight to meaningfully reduce ICP. This model also demonstrated that in the CWI arm if no or little weight loss was achieved in those with a high baseline weight an increase in ICP would be expected. Conclusions: There should be care when exposing women with IIH and BMI≥35kg/m2 to repeated cycles of lifestyle interventions that fail to achieve adequate weight loss, as this approach is unlikely to achieve sustained remission of disease. soozmollan@doctors.org.uk 51